Biostimulation can prime elicitor induced resistance of grapevine leaves to downy mildew - Jacquens, Lucile; Trouvelot, Sophie; Lemaitre-Guillier, Christelle; Krzyzaniak, Yuko; Clément, Gilles; Citerne, Sylvie; Mouille, Grégory; Moreau, Estelle; Héloir, Marie-Claire; Adrian, Marielle (Frontiers in Plant Science, 2022)
Using plant defense elicitors to protect crops against diseases is an attractive strategy to reduce chemical pesticide use. However, development of elicitors remains limited because of variable effectiveness in the field. In contrast to fungicides that directly target pathogens, elicitors activate plant immunity, which depends on plant physiological status. Other products, the biostimulants, can improve certain functions of plants. In this study, the objective was to determine whether a biostimulant via effects on grapevine physiology could increase effectiveness of a defense elicitor. A new methodology was developed to study biostimulant activity under controlled conditions using in vitro plantlets. Both biostimulant and defense elicitor used in the study were plant extracts. When added to the culture medium, the biostimulant accelerated the beginning of plantlet growth and affected the shoot and root development. It also modified metabolomes and phytohormone contents of leaves, stems, and roots. When applied on shoots, the defense elicitor changed metabolite and phytohormone contents, but effects were different depending on whether plantlets were biostimulated or controls. Defense responses and protection against Plasmopara viticola (downy mildew agent) were induced only for plantlets previously treated with the biostimulant, Therefore, the biostimulant may act by priming the defense elicitor action. In this study, a new method to screen biostimulants active on grapevine vegetative growth was used to demonstrate that a biostimulant can optimize the efficiency of a plant defense elicitor.